Temperature distribution investigation during friction stir welding (fsw) using smoothed-particle hydrodynamics (sph) - Meyghani, B. (Springer Science and Business Media Deutschland GmbH, 2020)
Fundamentally, heat is needed during friction stir welding (FSW) for joining materials together. This heat is mainly produced by the friction force which is a part of the force that is applied to the tool. Many researchers have tried to use finite element modelling for investigating the thermal and the material flow behaviour; however, the process large plastic deformation causes mesh distortion. To illustrate, the excessive mesh distortion should be considered as one of the key problems happening during the modelling of the process. In this paper, the thermomechanical behaviour of FSW is investigated using finite element modelling. The smoothed-particle hydrodynamics (SPH) method is used to solve the mesh distortion problem. The outcomes indicated that the temperature of the welding is around 524Â Â°C that is less than the welding material melting point. Finally, the outcomes are matched with some scientific papers which this issue confirms the accuracy of the simulated model. Â© Springer Nature Singapore Pte Ltd 2020.